Robotic Versus Laparoscopic Approach to Hiatal Hernia Repair: Results After 7 Years of Robotic Experience. Issue 9 (September 2020) - O'Connor, Sean C.; Mallard, Matthew; Desai, Shivani S.; Couto, Francisco; Gottlieb, Matthew; Ewing, Alex; Cobb, William S.; Carbonell, Alfredo M.; Warren, Jeremy A.
Introduction: Robotic hiatal hernia repair offers potential advantages over traditional laparoscopy, most notably enhanced visualization, improved ergonomics, and articulating instruments. The clinical outcomes, however, have not been adequately evaluated. We report outcomes of laparoscopic and robotic hiatal hernia repairs. Methods: A retrospective observational cohort study was performed of all hiatal hernia repairs performed from 2006 through 2019. Operative, demographic, and outcomes data were compared between laparoscopic and robotic groups. Discrete variables were analyzed with Chi-square of Fisher's exact test. Continuous variables were analyzed with Student's t test (mean) or Wilcoxon rank sum (medians). All analyses were performed using R statistical software. Results: Laparoscopic repair was performed in 278 patients and robotic repair in 114. More recurrent hernias were repaired robotically (24.5% vs 12.9%, P = .08). Operative times were no different between groups (175 vs 179 minutes; P = .681). Robotic repair resulted in significantly shorter length of stay (LOS; 2.3 vs 3.3 days; P = .003). Rate of readmission was no different, and there were no differences in acute complications. For patients with at least 1 year of follow-up, recurrence rates were lower after robotic repair (13.3% vs 32.8%; P = .008); however, mean follow-up is significantly longer after laparoscopic repair (23.7 ± 28.4 vs 15.1 ± 14.9 months; P < .001). Discussion: Robotic hiatal hernia repair offers technical advantages over laparoscopic repair with similar clinical outcomes.